Inflammatory myofibroblastic tumor of the pancreas in a dog. (November 2019) - Romanucci, Mariarita; Defourny, Sabrina V. P.; Massimini, Marcella; Bongiovanni, Laura; Aste, Giovanni; Vignoli, Massimo; Febo, Elettra; Boari, Andrea; Della Salda, Leonardo
A large, ill-defined, firm, multinodular mass involving the pancreas was confirmed on postmortem examination of a 5-y-old, male Rottweiler that died following acute respiratory distress syndrome, after a period of anorexia and lethargy. Histologically, the mass consisted of plump spindle cells admixed with a variable number of macrophages, lymphocytes, plasma cells, and neutrophils. Foci of coagulative necrosis and hemorrhage were also observed. Spindle cells strongly reacted to antibodies against vimentin, α–smooth muscle actin, and calponin, whereas desmin was expressed only mildly and focally. Pan-cytokeratin, KIT, glial fibrillary acidic protein, and S100 protein were nonreactive. Variable numbers of MAC 387–positive cells, CD3+ lymphocytes, and numerous blood vessels were also detected throughout the mass. Histologic and IHC findings were consistent with a diagnosis of inflammatory myofibroblastic tumor of the pancreas.